Generalized aspergillosis (clinico-morphological observations) - Sakal , H.O.; Horhol , N.I.; Potapov , S.M.; Naumova , O.V.; Voloshchuk , V.O. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Generalized aspergillosis is a severe invasive mycosis with high lethality and complex intravital diagnostics. The causative agents are mainly Aspergillus fumigatus, less often A. niger, A. flavus and others. Infection occurs mainly by the airborne transmission, affecting the lungs with subsequent hematogenous dissemination and development of multiple organ failure. Objective. By the example of clinical and morphological observations to attract attention and raise the awareness of pathologists concerning generalized aspergillosis. Methods. Pathomorphological examination of the generalized aspergillosis using histological methods. Results. The main problems of diagnostics are low informativity of standard X-ray and bacteriological methods, a lengthy wait of the cultural studies results and frequent false negative serologic tests. The most informative modern methods are considered to be high-resolution spiral computer-aided tomography, determination of the galactomannan antigen, bacteriological examination of sputum or biopsy material. The article presents two clinical and morphological cases of generalized aspergillosis with involvement of the lungs, kidneys, stomach, myocardium and brain. In both cases pathology was not diagnosed, what led to the ineffectiveness of treatment and fatal outcome. Pathomorphological studies confirmed A. fumigatus infection. Conclusions: 1. Doctors of any specialty who encounter diagnostically difficult cases of antibiotic-resistant diseases (diseases of the bronchopulmonary system, diseases of the ENT organs, septic conditions, etc.) must be alert for possible aspergillosis. 2. The existing problems of the antemortem clinico-laboratory diagnostics of aspergillosis require its improvement with the obligatory use of serological tests with determination of the galactomannan antigen level, bacteriology and microscopy of sputum, high-resolution spiral computer-aided tomography of organs of the chest and abdominal cavity which are the most informative modern examination methods for detecting generalized aspergillosis. 3. It is necessary to conduct a more in-depth study of biopsy and autopsy material with a detailed study of aspergillosis morphology.